Impacts of covid-19 on the management of household and recyclable solid waste. Case study: municipality of Araraquara (SP) - Morais, Mariana Sedenho de; Ventura, Katia Sakihama (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Covid-19 has triggered substantial changes in the lives of the world’s population, affecting solid waste management in both developed and developing countries. In Brazil, 37,949,844 people have been confirmed to be infected as of November 18, 2023 and the main form of transmission of the SARS-CoV2 virus was via saliva droplets. The virus can survive on metal or stainless steel surfaces for up to 9 days. The general goal was to analyze the impact of Covid-19 on the collection of household solid waste (HSW) and recyclable solid waste (RSW) in Araraquara (SP) from March 2020 to April 2022. The approach was of exploratory and case study nature, comprised of three stages: I) characterization of the study area; II) monitoring of cases of disease and social isolation; and III) analysis of the interface between the collection of HSW and RSW with Covid-19. The main results have indicated: I) the influence of social isolation and Covid-19 cases on the generation and composition of waste in the municipality; II) a decrease in the mass of HSW and RSW collected by -5.1% and -9% in 2020 compared to 2019; III) a reduction in the average amount of HSW and RSW collected in 2020, 2021 and 2022; and IV) an increase in the disposal of plastic materials, paper and cardboard due to the greater use of single-use packaging and utensils. The main contribution of this study was to point out recommendations to municipal authorities for preventive solid waste management in pandemic cases.